Determinants of economic fluctuations in the construction sec-tor - Wieslaw Matwiejczuk; Mariusz Gorustowicz (Institute of Economic Research (IER), 2017)
Awareness and ability to possibly eliminate the potentially adverse consequences of economic fluctuations can constitute an extremely important factor of the financial condition and competitive position of the company as well as the entire construction sector. Especially in the construction sector creating a catalog of fac-tors affecting economic fluctuations is important from the point of view of not only the economy but also the company. The analysis carried out in this article of situation fluctuations in the construction industry in recent years allow to specify the factors that largely determine the conditions for construction enterprises devel-opment and shaping their competitiveness. Research background: The specifics and operation conditions of enterprises including the construction sector companies cause sensitivity to economic fluctua-tions manifested in the cyclical disorders of economic activity level (business cy-cles). Background research work is to determine the effect of internal and external environment on a range of determinants of the economic situation fluctuations potentially occurring in the sphere of the construction sector. Purpose of the article: The aim of this article is to present the main factors affect-ing economic condition fluctuations in the construction sector and their impact on company operation. Methodology/methods: The following research methods and tools are used in this work: analysis and critique of literature, examination of documents, analysis and synthesis, descriptive statistics. Findings: The result of the study and documents analysis will include identifica-tion of factors affecting to the highest degree the economic fluctuations in the construction sector. These factors will be specified from among the macro-economic environment but mainly from the internal environment of the company. Developed proposals will be useful in building the short- and long-term operation strategy for both the construction companies and the entire sphere of the construc-tion sector.
Keywords: D24; E32; F60; L78; 330; economic situation; determinants; factors; internal environment; the construction sector